PP.26.21: DIFFERENT ASPECTS AND CHARACTERISTICS OF REFRACTORY AND RESISTANT HYPERTENSION OBSERVED IN A SPECIALIZED CLINIC. (June 2015) - Modolo, R.; De Faria, A.P.; Ritter, A.M.V.; Sabbatini, A.R.; Batista, N.; Brunelli, V.; Barbaro, N.R.; Almeida, A.; Moreno, H.
Abstract : Objective: Resistant hypertension (RH) is defined as BP levels that remain uncontrolled despite the use of at least 3 anti-hypertensive drugs, or controlled requiring the use of at least 4 drugs. Recently a new definition for a more extreme phenotype of RH (uncontrolled BP using at least 5 drugs) has emerged – the refractory hypertension. Although characteristics of the resistant hypertensive population are well established, little is known of this newly described subgroup. The aim of this study was to characterize subjects with refractory hypertension among RH and identify factors associated with it. Design and method: One hundred and sixteen (116) subjects with true resistant hypertension were enrolled from a specialized RH Clinic and divided into two groups according to the new definition: RH (n = 80), and refractory hypertension (RfH, n = 36), after protocoled 6-month follow-up. Subjects were submitted to echocardiography, 24h-ABPM and office BP measurements and biochemical analyses. Results: There were no difference between groups regarding age, gender and biochemical parameters. RfH subgroup had higher left ventricular mass index (LVMI, 127 ± 46 vs. 112 ± 34 g/m2, p = 0.04), presence of WCE (67% vs. 39%, p = 0.01) and were more likely black (61% vs. 26%, p < 0.001) compared with their counterparts. The use of antihypertensive drugs was higher in RfH group (5.6 ± 0.7 vs. 3.9 ± 0.6, p < 0.001), especially due to increased use of spironolactone (72% vs. 35%, p = 0.002) and β-blockers (89% vs. 63%, p = 0.02) in this group. Multiple logistic regression analysis demonstrated that: (1) WCE (OR = 3.23, 95% confidence interval-95%CI 1.12–9.27, p = 0.03), (2) black race (OR = 6.67, 95%CI 1.99–16.16, p < 0.001) and (3) left ventricular mass index (OR = 1.02, 95%CI 1.01–1.03, p = 0.04) were independent predictor of refractoriness (Table 1), adjusted for age and gender. Figure. No caption available. Conclusions: In conclusion, refractory and resistant hypertension present different patients characteristics, prevailing black race with higher LVMI and WCE. These phenotypic aspects can be useful for better understanding this harder-to-treat subgroup.